A Chimeric 18L1-45RG1 Virus-Like Particle Vaccine Cross-Protects against Oncogenic Alpha-7 Human Papillomavirus Types - Huber, Bettina (PLoS One, 2015)
Persistent infection with oncogenic human papillomaviruses (HPV) types causes all cervical and a subset of other anogenital and oropharyngeal carcinomas. Four high-risk (hr) mucosal types HPV16, 18, 45, or 59 cause almost all cervical adenocarcinomas (AC), a subset of cervical cancer (CxC). Although the incidence of cervical squamous cell carcinoma (SCC) has dramatically decreased following introduction of Papanicolaou (PAP) screening, the proportion of AC has relatively increased. Cervical SCC arise mainly from the ectocervix, whereas AC originate primarily from the endocervical canal, which is less accessible to obtain viable PAP smears. Licensed (bivalent and quadrivalent) HPV vaccines comprise virus-like particles (VLP) of the most important hr HPV16 and 18, self-assembled from the major capsid protein L1. Due to mainly type-restricted efficacy, both vaccines do not target 13 additional hr mucosal types causing 30% of CxC. The papillomavirus genus alpha species 7 (α7) includes a group of hr types of which HPV18, 45, 59 are proportionally overrepresented in cervical AC and only partially (HPV18) targeted by current vaccines. To target these types, we generated a chimeric vaccine antigen that consists of a cross-neutralizing epitope (homologue of HPV16 RG1) of the L2 minor capsid protein of HPV45 genetically inserted into a surface loop of HPV18 L1 VLP (18L1-45RG1). Vaccination of NZW rabbits with 18L1-45RG1 VLP plus alum-MPL adjuvant induced high-titer neutralizing antibodies against homologous HPV18, that cross-neutralized non-cognate hr α7 types HPV39, 45, 68, but not HPV59, and low risk HPV70 in vitro, and induced a robust L1-specific cellular immune response. Passive immunization protected mice against experimental vaginal challenge with pseudovirions of HPV18, 39, 45 and 68, but not HPV59 or the distantly related α9 type HPV16. 18L1-45RG1 VLP might be combined with our previously described 16L1-16RG1 VLP to develop a second generation bivalent vaccine with extended spectrum against hr HPV.